Measuring the divergent thinking ability in biology science process skills of elementary school students based on tutoring activities - Ikhsanudin Ikhsanudin; Bambang Subali (Edu Sains: Jurnal Pendidikan Sains dan Matematika)
Learning in the current era is often directed at developing creativity. Increasing creativity is very close to divergent thinking skills. This study aims at measuring the divergent thinking ability in biology science process skills of the sixth-grade students at elementary schools in one regency in relation to the tutoring activities along with the effect of gender and parent